Incapacitating Xanthomas - Gupta, Gunjan; Diwana, Vijay Kumar; Mahajan, Kunal; Chauhan, Rajesh; Thakur, Saru (Cardiology and Cardiovascular Medicine, 2017)
A 15 years old female presented with multiple gradually enlarging nodules over the limbs and buttock region for past 8 years. Patient was mainly concerned about swellings over her feet and hands, as these were so incapacitating that she was unable to do routine tasks like wearing shoes and writing. Her father and younger sibling had similar nodules but much smaller in size. Systemic examination was normal. Local examination revealed multiple yellowish brown, smooth surfaced painless xanthomas of varying size over gluteal region, bilateral knees,feet and hands. (Figure 1) Xanthomas between thumb and index finger, a pathognomic finding in homozygous familial hypercholesterolemia(HoFH) was also seen. (Figure 1a and 1b) Blood investigations revealed deranged lipid profile (total cholesterol of 710 mg/dl, low density lipoprotein (LDL) cholesterol of 620 mg/dl, high density lipoprotein cholesterol of 35 mg/dl and triglycerides of 115 mg /dl). Rest of the blood investigations were normal. X-ray bilateral knees, feet and hands revealed soft tissue swellings corresponding to soft tissue swellings.Typical clinical manifestations at a young age, lipidogram and positive family history in two first degree relatives confirmed the diagnosis of HoFH.[1] Genetic testing facility was not available Fortunately patient did not have any atherosclerotic or cardiac manifestations. She was started on high dose rosuvastatin and ezitimibe therapy.